The macroeconomic variables influence movement of stock market (KLCI) / Noor Amira Arshad and Nurhaida Osman - Arshad, Noor Amira; Osman, Nurhaida (Faculty of Business and Management, 2013)
The objective of this research is to identity the relationship between Kuala Lumpur Composite Index (KLCI) and macroeconomic variables which are exchange rate, inflation rate, money supply and interest rate. This research is study on how macroeconomic variables can affect the movement in stock markets. Yearly data from period of 1981 until 2011 have been used. This study adopts two models which are Single Linear Regression and Multiple Linear Regression. Based on the result, the exchanges rate, inflation rate, money supply and interest rate is significant with KLCI. Besides that, the exchanges rate, money supply and interest rate is positive correlated since only the inflation have negative correlated with stock market.